The Bubble of American Supremacy : Correcting the Misuse of American Power - Soros, George (New York Pcblic Affairs, 2004)
Presents an analysis of the Bush Administration's policy in Iraq, arguing that the Iraqi invasion has eroded the basic values of America at home and hurt its standing in the world.
Include Appendix and Index
Keywords: United States -- Diplomatic relations -- Balance of power -- Preemptive attack (Military science) -- Bush, George W. (George Walker), 1946-